Cervical lymphoepithelioma-like carcinoma with deficient mismatch repair and loss of SMARCA4/BRG1: a case report and five related cases - Yu Miyama; Tomomi Kato; Masayasu Sato; Akira Yabuno; Kosei Hasegawa; Masanori Yasuda (BMC, 2024)
Abstract Background We encountered a cervical lymphoepithelial carcinoma (LEC) possessing a predominantly solid architecture with deficient mismatch repair (dMMR) and loss of expression of the SWI/SNF (SWItch/Sucrose Non-Fermentable) chromatin remodeling complex subunit. This is the first case report of LEC with dMMR and loss of SWI/SNF complex subunit. Case presentation A 34-year-old woman presented at our hospital with menstrual irregularities and abnormal vaginal bleeding. Magnetic resonance imaging revealed an exophytic mass in the posterior uterine cervix. Biopsy specimens confirmed squamous cell carcinoma with a 2018 International Federation of Gynecology and Obstetrics (FIGO) uterine cervical cancer stage of IB2. In a subsequent conization specimen, the tumor appeared exophytic. Microscopically, the tumor cells formed a predominant solid architecture. Abundant lymphocytic infiltration was observed. The pathological diagnosis indicated human papillomavirus (HPV)-associated squamous cell carcinoma with LEC pattern and pT1b2. Immunohistochemically, high programmed death-ligand 1 (PD-L1) expression, dMMR, and loss of the switch/sucrose non-fermentable family-related, matrix-associated, actin-dependent regulator of chromatin subfamily member 4 (SMARCA4)/BRG1, an SWI/SNF complex subunit, were observed. The patient underwent a radical hysterectomy and is alive without disease one year and five months later. Our analysis of five additional LEC cases revealed a consistent association with high-risk HPV and elevated PD-L1 expression. In addition to the present case, another patient exhibited dMMR. The SWI/SNF complex was retained except in the present case. The prognosis was favorable in all cases. Conclusions This unique case of LEC with dMMR suggests a distinct clinical entity with potential immunotherapy implications. Analysis of the other five LEC cases revealed that LEC was immune hot, and immune checkpoint inhibitors may be effective. The two dMMR cases showed loss of MLH1 and PMS2 expressions, and prominently high tumor PD-L1 expression. In those cases, dMMR might have contributed to the morphological characteristics of LEC.